THE ROLE OF INCLUSIVE FINANCE IN REDUCING ECONOMIC INEQUALITY - Loso Judijanto; Oskar Hutagaluh (CV. Adiba Aisha Amira, 2024)
Economic inequality is one of the global challenges that continues to be a concern for many countries. In an effort to address this issue, inclusive finance has emerged as a promising strategy. This study uses literature research method. The results show that inclusive finance has significant potential in reducing economic inequality through several mechanisms. First, by expanding access to formal financial services, inclusive finance enables low-income groups to save, obtain credit, and make investments. Second, inclusive finance programmes can improve financial literacy and encourage better financial decision-making. Third, inclusive finance supports the development of micro, small and medium enterprises (MSMEs), which play an important role in job creation and inclusive economic growth.